The Role of Agricultural Extension in Diffusion and Adoption of Biological Control Methods for Tomato Growers in Villages of Matrouh Governorate - Mohamed, Abdu Omran; Kamel, Fekry Kamal; Allam, Yousria Ahmed; Mohamed, Ismail Abdel-Malik (Asian Journal of Agriculture and Rural Development, 2021)
This research aimed to define the role of agricultural extension in the process of Diffusion and adoption of biological control methods among tomato growers in Matrouh Governorate, Egypt, and also to define the relationship between their role in agricultural extension in Diffusion and adopting biological Control methods for tomato growers and some independent variables .The research was conducted in Matrouh Governorate using a random sample of 323 farmers, representing 16% of the total research cohort amounting to 2050 farmers; the data were collected using a questionnaire in September 2019. Data wereanalyszed using a statistical program, arithmetic mean, and the simple correlation coefficient of Pearson (r). The results are also presented in tabular form using frequencies and percentages.The main results of the research are as follows:the majority of farmers (82.97%) stated that the role of agricultural extension in diffusion and adoption methods of biological control among tomato growers was low, while 15.17% said that agricultural extension plays an intermediate role and 1.86% said it played a key role.There is a positivecorrelation at the 0.01 level of significance between the level of farmers' adoption of biological control methods as an dependent variable and each of the following independent variables: participation in local development organizations, social participation, satisfaction with life in the region, and attitudes towards agricultural innovations; and there is a positive correlation at the 0.05 level of significance with the levels of modernization and farmers' education.